ENVIRONMENTAL PROBLEMS OF WATER RESOURCES AT THE PRESENT STAGE - Madraim Khasanovich Sarikulov; Nurmatov Begzod Khasan og’li (Modern American Journals, 2025)
This article examines water resources as a source of drinking water for all inhabitants of the globe in the context of socio-economic development, energy and food production, healthy ecosystems, and human survival. It also examines issues related to improving the provision of clean water to populations in various countries. Furthermore, it highlights the problem of water scarcity, taking into account the demographic growth of the planet, which has significantly increased water consumption. The article also discusses the factors that contributed to water scarcity, which subsequently led to a deterioration in living conditions and slowed the economic development of countries experiencing water shortages.
Keywords: Water resources, water scarcity, water disaster, population migration, UN classification, groundwater and surface water, water erosion, spread of infections, waste-free technologies, radioactive and toxic waste, atmospheric oxygen.